2018
DOI: 10.20494/tm/5/2/5
|View full text |Cite
|
Sign up to set email alerts
|

Baromfihús fogyasztási és vásárlási szokások elemzése szocio-demográfiai tényezők függvényében

Abstract: The consumption of poultry is an important source of nutrition, so it is a basic need for everyday food conception. To supply the population is not only a sensitive social question, but also a question of national health. The aim of this study is to reveal the connection between the preference of poultry and the basic socio-demographic factors and highlight the circumstances of purchasing this type of meat. In order to understand the preference of poultry, a large sample quantitative (N=1 023 respondents) stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Ebből is fakad, hogy a helyi termék fogalmával szoros kapcsolatban áll. A helyi termék fogalma bár szintén nincs szigorú szabályokhoz kötve, de fő jellemzője a rövid ellátási láncban tör-ténő értékesítése (Huszka, 2008;Peters et al, 2008;Brain, 2012;NAK, 2016;Granvik et al, 2017). A helyi termék és a rövid ellátási lánc emellett fontos hívószavai lettek a fenntartható élelmiszer-ellátási láncokat vizsgáló nemzetközi tanulmányoknak (Morgan, 2010;Granvik, 2012;Garnett, 2014;Baldy, 2019, Kotler, 2020.…”
Section: Bevezetésunclassified
“…Ebből is fakad, hogy a helyi termék fogalmával szoros kapcsolatban áll. A helyi termék fogalma bár szintén nincs szigorú szabályokhoz kötve, de fő jellemzője a rövid ellátási láncban tör-ténő értékesítése (Huszka, 2008;Peters et al, 2008;Brain, 2012;NAK, 2016;Granvik et al, 2017). A helyi termék és a rövid ellátási lánc emellett fontos hívószavai lettek a fenntartható élelmiszer-ellátási láncokat vizsgáló nemzetközi tanulmányoknak (Morgan, 2010;Granvik, 2012;Garnett, 2014;Baldy, 2019, Kotler, 2020.…”
Section: Bevezetésunclassified
“…A Hungarian study found that the preference for poultry meat depends on the consumer's age and place of residence, with the preference for poultry meat being highest among people aged 50 and over, young people under 34 and those living in cities with county status. People in better financial circumstances consume more poultry meat than people with lower social status (Huszka et al, 2018). Although turkey meat has many physiological advantages, it is still not a very popular product among Hungarian consumers.…”
Section: )mentioning
confidence: 99%
“…Another survey, which examined the frequency of poultry meat purchases by gender, found that women purchase more of this meat weekly than men do. The increase in the frequency of poultry meat purchases can be associated with higher educational attainment (Szakály, 2016;Huszka et al, 2018). After analysing the past, it is worth looking at the trends that will determine future purchasing habits.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations